Hubungan pengetahuan, sikap, dan dukungan sekolah dengan kepatuhan konsumsi tablet tambah darah pada remaja putri - Salsabiila Salsabiila; Muammar Iksan; Nur Husnul Khatimah; Alkhair Alkhair (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Adolescent girls are at risk of anemia due to increased iron requirements during growth and menstruation. Although the iron supplementation program has been implemented, adherence rates regarding the consumption of these supplements remain low. Purpose: To determine the relationship between knowledge, attitudes, and school support and adherence to iron supplementation consumption among adolescent girls. Method: A quantitative study with a cross-sectional design was conducted involving 89 respondents selected via purposive sampling. This research was conducted at State Islamic High School 2 Bima City in April and May 2026. Data were collected using questionnaires and analyzed using the Chi-Square test and multiple logistic regression. Results: Most respondents possessed good knowledge (69.7%) and fair attitudes (59.6%) but perceived school support as inadequate (71.9%); additionally, 52.8% of respondents were non-adherent to consumption. Knowledge was not associated with adherence (p=0.096; OR=2.3), whereas attitudes (p=0.004; OR=3.8) and school support (p=0.020; OR=1.4) showed significant associations. Attitude was the most dominant factor influencing adherence. Conclusion: There is no significant relationship between knowledge and adherence to Iron Supplementation consumption among adolescent girls. Conversely, there are significant relationships between attitudes and school support and adherence to consumption among adolescent girls. Suggestion: Schools need to strengthen education and monitoring regarding consumption. Future research is advised to include factors such as family support, peer support, motivation and side effects. Keywords: Attitude; Compliance; Iron-Folic Acid Tablets; Knowledge; School Support.